High Glass Transition Temperature Renewable Polymers via Biginelli Multicomponent Polymerization. Issue 7 (22nd January 2016) - Boukis, Andreas C.; Llevot, Audrey; Meier, Michael A. R.
Abstract : A novel and straightforward multicomponent one‐pot Biginelli polycondensation employing urea, dialdehydes, and diacetoaceates as AA‐type monomers is reported. The resulting Biginelli‐type polymers (polyDHMPs) display high glass transition temperatures ( T g ) up to 203 °C. Furthermore, the T g can be tuned by variation of the components and all monomers used for the polymerizations can be obtained from renewable resources. Abstract : A novel and straightforward one‐pot multicomponent polycondensation method was established in this work. The Biginelli reaction is a versatile multicomponent reaction of an aldehyde, a β‐ketoester (acetoacetate) and urea, which can all be obtained from renewable resources, yielding diversely substituted 3, 4‐dihydropyrimidin‐2(1H)‐ones (DHMPs). In this study, renewable diacetoacetate monomers with different spacer chain lengths (C3, C6, C10, C20) were prepared via simple transesterification of renewable diols and commercial acetoacetates. The diacetoacetate monomers were then reacted with renewable dialdehydes, i.e., terephthalaldehyde and divanillin in a Biginelli type step‐growth polymerization. The obtained DHMP polymers (polyDHMPs) displayed high molar masses, high glass transition temperatures ( T g ) up to 203 °C and good thermal stability ( T d5% ) of 280 °C. The T g of the polyDHMPs could be tuned by variation of the structure of the dialdehyde or the diacetoacetate component.